2020
DOI: 10.1002/hpja.374
|View full text |Cite
|
Sign up to set email alerts
|

Core and peripheral organisations in prevention: Insights from social network analysis

Abstract: Issue: Formal (eg funded) community-level organisational collaborations are becoming more common in prevention. Rapid methods to assess organisational relationships could allow us to consider the significance of any pre-existing relationship patterns in communities that might impact on collaboration effectiveness. Insights may identify new options for practice. Methods:We used social network analysis to study organisations engaged in prevention but not (yet) part of a formal purposive collaboration. Within a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…These included size, number of connections, cohesion (level of participation, density, and centralization), function (information sharing or referrals), and integration. 16,17,22,58-90 Eight studies identified organizations central to the network and/or network brokers (organizations serving as a bridge between other organizations) and characterized how those organizations positively contribute to network development. Another 5 studies identified and characterized sub-networks which included smaller groups of organizations within the overall network.…”
Section: Resultsmentioning
confidence: 99%
“…These included size, number of connections, cohesion (level of participation, density, and centralization), function (information sharing or referrals), and integration. 16,17,22,58-90 Eight studies identified organizations central to the network and/or network brokers (organizations serving as a bridge between other organizations) and characterized how those organizations positively contribute to network development. Another 5 studies identified and characterized sub-networks which included smaller groups of organizations within the overall network.…”
Section: Resultsmentioning
confidence: 99%
“…To complicate matters further, networks that encourage or support unhealthy behaviours may also provide positive benefits to network members such as social support, recognition, and status (Dolan, 2014;Flores et al, 2013;Lohan, 2007). A central focus of community development and capacity building, therefore, becomes the creation of relationships, where links are absent or otherwise not achieving community needs (Held et al, 2020). For these issues to be detected and managed, health workers need funding to be constantly 'on the ground'.…”
Section: The Role Of Social Relationshipsmentioning
confidence: 99%
“…Previous studies on intersectoral action have often concentrated on the factors that may influence cooperation in a network (e.g., organizational aspects or leadership) [3,7,[45][46][47][48][49][50][51]. Several studies have analyzed networks (formalized and non-formalized) with regard to their structure and statistical measurements, without pointing out the roles and influences of certain actors, like we did in this study [52][53][54][55]. Other studies have focused on the evaluation of community partnerships and corresponding health outcomes and impacts [46,56,57].…”
Section: Discussionmentioning
confidence: 93%